Customer Satisfacion as A Predictor of Repurchase Intention Abeglass Using The customer Satisfaction Index - Mia Ayu Yulianti Hasanah; Nenden Kostini; Ratih Purbasari (Dinasti International Journal of Education Management And Social Science, 2024)
Customer satisfaction is a key factor in determining whether consumers will return to buy a product or use a particular service. To build long-term relationships with customers, customer satisfaction is needed so that it can encourage repurchase intention. This is very important in an increasingly competitive and dynamic business world. The point of this research is to explore the influence of customer satisfaction on the repurchase intention of Abeglass' domestic customers and measure the level of Abeglass's Customer Satisfaction Index. This research uses a quantitative approach with a descriptive-verification research type. The Customer Satisfaction Index (CSI) method and simple linear regression are the analysis systems used in this research. The research results show that customer satisfaction influences repurchase intention for Abeglass products by 60.4%, with the remaining 39.6% influenced by other factors. The Customer Satisfaction Index results were 89.57% which were interpreted as indicating very satisfied criteria. Apart from that, there is also a gap in the assurance dimension of -0.35.